Quelques remarques théoriques et pratiques sur la traduction du français vers le polonais dans l’approche orientée objets - Śmigielska, Beata (Neophilologica, 2014)
The article is devoted to the problem of translation from French into Polish from the perspective of the object oriented approach proposed by Wiesław Banyś. The author takes into consideration some of the problems, both of theoretical and practical nature, which appear while working on the formation of contrastive lexical database for automatic translation of texts. While analyzing specific chosen examples which may cause different kinds of problems in the description, the author offers their interpretations in the target language in accordance with the adopted approach.